RESPONS PERTUMBUHAN TANAMAN JAGUNG (Zea Mays L.) TERHADAP PEMBERIAN BEBERAPA DOSIS PUPUK HAYATI TRICHODERMA SP. - Sheli Mustikasari Dewi; Nurma Yanti Ningtyas, Dewi; Siti Amalia, Istia; Arif Malik Ramadhan , R. (Jurnal Biogenerasi, 2024)
Corn is a leading commodity sector of food crops that are useful and have high economic value to be cultivated or developed. There needs to be an effort to increase corn production, one of which is by fertilizing. The use of biological agents to provide biofertilizers that are more useful for plants is the most feasible alternative in an effort to increase the availability of nutrients in the soil. One biological agent that has the potential to help plant growth is the fungus Trichoderma sp. The purpose of this study was to see the growth response of corn plants to the application of Biofertilizer Trichoderma sp. with various dosages. The research was conducted from November 2023 to January 2024 at the Rawasari experimental garden, Kel. Munjuljaya, Purwakarta Regency. The study used a Group Randomized Design (RAK) with 5 dose treatments of Trichoderma sp., namely: 0 gr; 15 gr; 30 gr; 45 gr; and 60 gr. There are 5 treatment combinations with 5 repetitions. Observation variables are growth components (plant height, number of leaves, stem diameter and flowering age). The results showed that the best response growth component was 60 gr treatment dose of Trichoderma sp. against plant height (78.13 cm), number of leaves (11.52). stem diameter (2.8 cm) and flowering age (48.02 days).